If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1464 = 24(p + 25) Reorder the terms: 1464 = 24(25 + p) 1464 = (25 * 24 + p * 24) 1464 = (600 + 24p) Solving 1464 = 600 + 24p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-24p' to each side of the equation. 1464 + -24p = 600 + 24p + -24p Combine like terms: 24p + -24p = 0 1464 + -24p = 600 + 0 1464 + -24p = 600 Add '-1464' to each side of the equation. 1464 + -1464 + -24p = 600 + -1464 Combine like terms: 1464 + -1464 = 0 0 + -24p = 600 + -1464 -24p = 600 + -1464 Combine like terms: 600 + -1464 = -864 -24p = -864 Divide each side by '-24'. p = 36 Simplifying p = 36
| 0.3x+(0.2x-0.5)+0.2(x+2)=1.3 | | 8-1/5(4-630) | | x/6=9.1 | | 9x=320 | | 3(x+4)=6x+8-3x+4 | | 1x+7=27 | | 6b^2+23b+7= | | 3+6x*2=5+2x*2 | | -8(k+6)=-5k | | 4b-12=8b+6 | | 2x+10+3x+13+3x+13=180 | | 16-x*-6=-84 | | h=-4.9t^2+55t | | 10x=96 | | X/23=18 | | 3x+5x-3=2(4x+4) | | 2m+5n+6-4= | | 18+4v=36 | | 3(11)+10=22 | | 1/4y-3=-11 | | 3x+7y=-56 | | 3xy-xy+2a= | | x/(-6)=13 | | 2x+10=3x+13 | | -7(k+9)=9(k-5)-1k | | 7v+40=-8(7v-5) | | -4t-1/3t | | 2(a-2)=2a-4 | | 8(x+1)+7x=-82 | | 26+8g=5 | | in(x)-in(13)=0 | | 2x/2=10 |